Hydrogen Bond Networks in Binary Mixtures of Water and Organic Solvents - Stehle, Simon; Braeuer, Andreas Siegfried (Journal of Physical Chemistry B, 2019)
We here present an approach for the optical in situ characterization of hydrogen bond networks (HBNs) in binary mixtures of water and organic solvents (OSs), such as methanol, ethanol, and acetonitrile. HBNs are characterized based on (i) the analysis of experimental molar Raman spectra of the mixture, (ii) partial molar Raman spectra of the mixture constituents, and (iii) computed ideal molar Raman spectra of the mixture. Especially, the consideration of the partial molar Raman spectra provides insights into the development of hydrogen bonds of molecules of one species with their neighbors. The obtained Raman spectra are evaluated with respect to the centroid of the symmetric stretching vibration Raman signal of water and to the hydroxyl stretching vibration of alcohols. We show the influence of composition and temperature on the development of the HBN of the mixtures, the HBN of water, and the HBN of the OS molecules.
CRIS-Team Scopus Importer:2019-06-04